A novel circFMN2 promotes tumor proliferation in CRC by regulating the miR-1182/hTERT signaling pathways. (20th December 2019) - Li, Yongchao; Li, Changfeng; Xu, Ruisi; Wang, Yun; Li, Dandan; Zhang, Bin
Abstract: Background: Circular RNAs (circRNAs) are a class of non-coding RNAs broadly expressed in cells of various species. However, the molecular mechanisms that link circRNAs with colorectal cancer (CRC) are not well understood. In the present study, we attempted to provide novel basis for targeted therapy for CRC from the aspect of circRNA–microRNA (miRNA)–mRNA interaction. Methods: We investigated the expression of circRNAs in five paired CRC tissues and adjacent non-tumor tissues by microarray analysis. Differentially expressed circRNAs were identified between CRC tissues and non-cancerous matched tissues. We focused on hsa_circ_0005100, which is located on chromosome 1 and derived from FMN2, and thus we named it as circFMN2. The expression of circFMN2 was detected in 88 CRC tissues and cell lines by quantitative real-time PCR. Functional assays were performed to evaluate the effects of circFMN2 on proliferation in vitro, and on tumorigenesis in vivo . The relationship between circFMN2 and miR-1182 was confirmed by luciferase reporter assay. Results: circFMN2 was found to be significantly up-regulated in CRC tissues and cell lines. Moreover, knockdown of circFMN2 significantly inhibited cell proliferation and migration in vitro . Bioinformatics analysis predicted that there is a circFMN2/miR-1182/hTERT axis in CRC progression. Dual-luciferase reporter system validated the direct interaction of circFMN2, miR-1182, hTERT. Western blot verified that inhibition of circFMN2 decreased hTERT expression. Importantly, we demonstrated that circFMN2 was up-regulated in serum exosomes from CRC patients. Conclusion: In conclusion, circFMN2 is a central component linking circRNAs to progression of CRC via an miR-1182/hTERT axis.